Air Purification Using Polymer Fiber Filters. Issue 3 (1st December 2021) - Chai, Mengnan; Tong, Wangshu; Wang, Zhihao; Zhao, Shifeng; Zhang, Yihe
Abstract: Polymer fiber filters, with their high surface area, low cost, and easy large‐scale manufacturing, are widely used in air purification. These filters have been combined with various types of functional nanoparticles to endow them with electrostatic adsorption, photocatalysis, electrocatalysis, photoelectrocatalysis, or antibacterial properties, and improve their filtering performance. In this study, a summary of the research on single polymer and polymer composite filters for highly efficient air purification is presented. In single polymer filters, polar groups in the polymer chains, a rich porous structure, and electret process improve their removal capability. In polymer composite filters, metal–organic frameworks, porous particles, and electret materials as fillers improve the physical adsorption of the materials, while the use of photocatalysts, electrocatalysts, photoelectrocatalysts, and antibacterial agents as functional fillers endows the filters with additional chemical reactions for the complete degradation of gas and microorganism pollutants. Finally, the challenges that remain in the development of polymer filters for use in air purification are also discussed in terms of material type and fabrication technology. It is expected that polymer filters with tunable surface properties and multifunctions can realize highly efficient air purification with low energy consumption. Abstract : This review introduces several kinds of polymer fiber filters and discusses the effects of polymer filters on air pollutant removal. The removal performance of the polymer filters can be enhanced by additional function, such as electrostatic adsorption, photocatalysis, electrocatalysis, or photoelectrocatalysis. The particulate matter, volatile organic compounds, inorganic gases, and microorganisms can be removed effectively by such functional polymer filters.